Agency, Structure and the Power of Global Health Networks - Jeremy Shiffman (Kerman University of Medical Sciences, 2018)
Global health networks-webs of individuals and organizations linked by a shared concern for a particular condition-have proliferated over the past quarter century. In a recent editorial in this journal, I presented evidence that their effectiveness in addressing four challenges-problem definition, positioning, coalitionbuilding and governance-shapes their ability to influence policy. The editorial prompted five thoughtful commentaries that reflected on these and other challenges. In this follow-up editorial, I build on the commentaries to suggest ways of advancing research on global health networks. I argue that investigators would do well to consider three social theory-influenced global governance debates pertaining to agency-the capacity of individuals and organizations to act autonomously amidst structural constraints. The three debates concern the relationship between agency and structure, the power of ideas vis-à-vis interests and material capabilities, and the level of influence of non-state actors in a global governance system that most scholars identify as state-dominated. Drawing on these debates, I argue that rather than presume global health network influence, we need to find more robust ways to investigate their effects. I argue also that rather than juxtapose agency and structure, ideas and interests and non-state and state power, it would be more productive to consider the ways in which these elements are intertwined.